Procedures for developing rail revenue contribution by commodity and territory: year 1964 - Interstate Commerce Commission (Washington, D.C. Interstate Commerce Commision, 1967)
The book explains the procedures for developing Rail Revenue Contribution. The term revenue contribution as used in this study refers to the amount by which carload revenues resulting from the rate structure exceeded or failed to meet the out-of-pocket costs
II 14/01/2019
Loans